Pengaruh Model Pembelajaran Problem Based Learning (PBL) Dan Project Based Learning (PJBL) Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ekonomi Dalam Implementasi Kurikulum Merdeka - Milenio Michael Kojongian; Allen A. Ch Manongko; Herman Philips Dolonseda (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to analyze the influence of Problem Based Learning (PBL) and Project Based Learning (PjBL) learning models on students' learning motivation in economics subjects in the implementation of the Independent Curriculum. This research method uses a quantitative approach with experimental methods. The study population was all 10th-grade students at SMA Negeri 1 Manado, with the research sample determined using a purposive sampling technique. Data collection was conducted through a learning motivation questionnaire and observation of the learning process. Data analysis was conducted using descriptive and inferential statistical tests.The research results show that the implementation of Problem-Based Learning and Project-Based Learning models has a positive and significant impact on student learning motivation. Learning models that emphasize activity, collaboration, and problem-solving can increase student engagement in the economics learning process. Therefore, the implementation of PBL and PjBL models can be an effective strategy for increasing student learning motivation during the implementation of the Independent Curriculum